Profit Sharing Ratio, BI Rate, and Inflation to Improve Mudharabah Deposits - Fitri Dhivi Lovika; Nonie Afrianty; Rizky Hariyadi (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
Introduction/Main Objectives: This study investigates how the profit-sharing ratio, BI Rate, also inflation affect level of Mudharabah deposits held in Islamic Commercial Banks (ICB) in Indonesia. Background Problems: Mudharabah deposit growth may be influenced by internal banking policies and macroeconomic conditions. Novelty: This study examines nine ICB during 2020–2024. Research Methods: Study utilizes a quantitative approach by analyzing secondary data through multiple linear regression based on 45 observations. Finding/Results: The findings indicate that only the profit-sharing ratio significantly effects on Mudharabah deposits, whereas BI Rate also inflation have no significant impact. Conclusion: The profit-sharing ratio plays an important role in increasing Mudharabah deposits in Islamic banking.